Strategi Pendidikan Pancasila dalam Membentuk Nilai-Nilai Kebangsaan pada Anak Usia Dini - Muh. Zainul Arifin (AL-MIKRAJ : Jurnal Studi Islam dan Humaniora, 2023)
Pancasila education plays a very important role in shaping national values in early childhood. The purpose of writing this research is to analyze the urgency and strategy of Pancasila education in forming national values in early childhood. This study uses the literature review method to analyze relevant studies on Pancasila educational strategies in forming national values in early childhood. Relevant literature sources are identified and analyzed using content analysis techniques. This study aims to gain an in-depth understanding of effective strategies in Pancasila education and their influence on the formation of national values in early childhood. The result of this work is that the inculcation of national values in early childhood is important for forming responsible characters and strengthening national identity, as well as preparing for a better nation's future. Pancasila education in early childhood is important in forming national values through reflective and transinternal strategies, with the active role of teachers, parents and the surrounding environment to create supportive intensive stimulation.